PS2 - 197 DICER Governs Characteristics of Glioma Stem Cells and the Resulting Tumors in Xenograft Mouse Models of GBM. (18th October 2016) - Mansouri, S.; Singh, S.; Alamsahebpour, A.; Burrell, K.; Li, M.; Karabork, M.; Ekinci, C.; Solaroglu, I.; Chang, J.T.; Aldape, K.; Zadeh, G.
Abstract : The RNAse III endonuclease DICER is a key regulator of microRNA (miRNA) biogenesis and is frequently down-regulated in a variety of malignancies. We characterized the role of Dicer in glioblastoma (GB), specifically demonstrating its effects on the ability of glioma stem-like cells to form tumors in a mouse model of GB. DICER silencing in glioma stem-like cells (GSCs) reduced their stem cell characteristics, while tumors arising from these cells were more aggressive, larger in volume, and displayed a higher proliferation index and lineage differentiation. The resulting tumors, however, were more sensitive to radiation treatment. Our results demonstrate that DICER affects the tumorigenic potential of GSCs, providing a platform for analysis of specific relevant miRNAs and development of potentially novel therapies against GB.